Theoretical analysis of the adaptive system for suppression of the interference concentrated on a spectrum - Hutsol, Taras; Mуkhaylova Lyudmyla; Kozak, Oleksandr; Kosulina, Natalia; Cherenkov, Aleksandr (Technology audit and production reserves, 2017)
The object of research is the process of interference suppression in a passive radiometric receiver, centered over the interference spectrum, with a random or varying frequency. Noise immunity can be increased by means of special circuits preventing the receiver from overloading and using differences in the characteristics of useful signals and interference to suppress the latter. As a rule, the frequency of noise oscillation is never accurately known and, in addition, the actual interference is never purely harmonic. Therefore, it became necessary to theoretically consider the degree of interference suppression by the input circuit of the radiometer at an unknown value of the interference frequency and the finite width of the spectrum, and also theoretically substantiate possible ways of constructing adaptive devices for suppressing real narrow-band noise. An expression is obtained for the suppression coefficient of the interference concentrated on a spectrum, which shows that the interference will be suppressed automatically for the optimal choice of the parameters ka, τ, T of the servo system. In the paper, a functional diagram of a radiometric receiver is presented, which uses an adaptive system to suppress the spectrum-centered interference. The adaptive system is based on the inclusion in the radiometric receiver circuit of additional compensating circuit interference. The interference compensating circuit makes it possible to increase the sensitivity of the receiver to 10-20 W with an accuracy of 0.1 ºC and a response rate of 2...4 s. In addition to interference suppression, the compensating link after the intermediate frequency amplifier is provided with interference suppression and an input circuit. In this case, the overall amplification in the noise immunity of the radiometric receiver in comparison with the compensating receiver, as calculations for typical characteristics show, will not be worse than 30 dB.